Zoonotic importance of cryptosporidiosis among some animals at Gharbia Province in Egypt - El-Hohari, A H; Abdel-Latif, A M (The Indian Journal of Animal Sciences, 2012)
A survey of cryptosporidiosis was carried out in some animals and human beings in contacts. Faecal specimens ( 180) from patients suffering with gastroenteritis at Gharbia province in Egypt were screened for cryptosporidium oocysts. The oocysts were detected in 9 patients (5.0%). Faecal specimens (44) were collected from the households living with the patients who showed cryptosporidiosis by laboratory investigation. The oocysts were detected in 2 of these households. Faecal samples (223) were collected from different animal species (calves 45, dogs 25, cats 16, sheep 52, goats 35, pigeon's and chicken's droppings 35) living in contact with patients who showed cryptosporidiosis,15 of these samples were soil contaminated with dog and cat excreta, the oocysts were detected in one of these samples.